2016
DOI: 10.1038/srep19245
|View full text |Cite
|
Sign up to set email alerts
|

Flavone synthases from Lonicera japonica and L. macranthoides reveal differential flavone accumulation

Abstract: Flavones are important secondary metabolites found in many plants. In Lonicera species, flavones contribute both physiological and pharmaceutical properties. However, flavone synthase (FNS), the key enzyme responsible for flavone biosynthesis, has not yet been characterized in Lonicera species. In this study, FNSII genes were identified from Lonicera japonica Thunb. and L. macranthoides Hand.-Mazz. In the presence of NADPH, the recombinant cytochrome P450 proteins encoded by LjFNSII-1.1, LjFNSII-2.1, and LmFNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 53 publications
(76 reference statements)
2
50
0
Order By: Relevance
“…2(b)]. This result agrees with previous data [21][22][23][44][45][46], verifying our physical interpretation. The pseudospin-polarized interface states are ideal phonon conduction channels for topological pseudospin transport.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…2(b)]. This result agrees with previous data [21][22][23][44][45][46], verifying our physical interpretation. The pseudospin-polarized interface states are ideal phonon conduction channels for topological pseudospin transport.…”
supporting
confidence: 93%
“…Therefore, Dirac states at the K and K ′ couple with each other, resulting in exotic physics in the distorted graphene, like chiral symmetry breaking, charge fractionalization, soliton, etc [41][42][43]. Recently, Wu et al theoretically proposed the realization of QSH-like states in a Kekulé lattice for photons [44] and electrons [45,46]. The proposal was soon generalized for acoustic systems that were examined experimentally [21][22][23].…”
mentioning
confidence: 99%
“…Recently, such a modulated structure has been revisited in the context of topological phases protected by crystalline symmetries. [12][13][14][15][16][17] Indeed, it has been found that the single-orbital tight-binding model hosts a topological crystalline insulator, accompanied by characteristic edge states 13,14) as a typical example of the bulk-edge correspondence. 18) Such an implementation of the topological nature is also applied to photonic crystals.…”
Section: Introductionmentioning
confidence: 99%
“…1, in which we assign intra-hexagon hopping t 0 = t+δ for black bonds and inter-hexagon hopping t 1 = t − δ for red bonds. This modulation gaps out Dirac cones of the original honeycomb lattice model through the coupling between the Dirac cones at the K and K' points in the Brillouin zone [29][30][31]. Importantly, the states near zero energy are described by a massive Dirac equation where the sign of the mass term can be flipped by changing the ratio between |t 0 | and |t 1 |, or the sign of δ.…”
mentioning
confidence: 99%